Juridical Study of Liability Execution Auctions Limit Value Below the Value of Loans - Yekti Mumpuni; Ibnu Arly (UIN Sunan Gunung Djati, 2022)
Credit agreements made by banks with customers are a function of banks as channeling funds to the public, besides that banks also function as collectors of public funds. More results obtained from the distribution of funds than the collection is income for the bank which is known as the spread. However, focusing on spreads poses a risk that the customer (debtor) will not be able to collect it so that it is detrimental to the bank, therefore banks must apply the precautionary principle in extending credit to customers. If the debtor cannot be billed, the bank can execute the guarantee provided by the debtor as one of the requirements for obtaining credit, this is to cash the guarantee as a payment for bills that are not paid by the debtor. One way of execution permitted by law is through an auction of mortgage execution by way of registering the auction to the KPKNL and will be carried out by a Class I Auction Officer. In the auction there are two prices, namely the limit price and the auction price, each of which is the minimum bid price. auction offered by the seller (auction requester) and the maximum price of the auction offer given by the auction participant and is the winner of the auction. The problem that often occurs in the implementation of this auction is the determination of the limit price which is considered too low by the debtor so that it is detrimental to the debtor to obtain the maximum value for the auction, resulting in a lawsuit in court for the cancellation of the auction results due to unlawful acts. This happened in the decision of the District Court Number 144/Pdt.Bth/2020/PN Sby where Sri Suarwati et al., as the plaintiffs, filed a lawsuit to cancel the auction of the execution of mortgage rights for alleged unlawful acts to determine the collateral limit value that was too low for the collateral assets. resulting in the defendant being in debt even though the collateral has been auctioned off and released from it. Through the principle of justice, the auction institution should be able to provide happy results for all parties so that the KPKNL as the official State institution holding the mortgage execution auction and the Class I Auction Officer must be active and not only based on procedural completeness, but also be able to read the auction that will be submitted. the implementation of whether there is a violation of law in it because the deed of the minutes of auction issued is included in the authentic deed.